2023
DOI: 10.3389/fpls.2023.1130471
|View full text |Cite
|
Sign up to set email alerts
|

Pinus massoniana somatic embryo maturation, mycorrhization of regenerated plantlets and its resistance to Bursaphelenchus xylophilus

Abstract: Pine wilt disease, caused by the pine wood nematode (PWN, Bursaphelenchus xylophilus), is a major quarantine forest disease that poses a threat to various pine species, including Pinus massoniana (masson pine), worldwide. Breeding of PWN-resistant pine trees is an important approach to prevent the disease. To expedite the production of PWN-resistant P. massoniana accessions, we investigated the effects of maturation medium treatments on somatic embryo development, germination, survival, and rooting. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…This study showed that various seed families exhibited significantly different capacities in initiating EC, with range 1.11-27.78%, and family 7# was more responsive than families 27# and 30#. Similar significant differences in EC initiation capacity among different pine families were also observed in P. elliottii (Liao and Amerson 1995a;Liao and Amerson 1995b;Yang et al 2020), P. taeda (Tang et al 2001;Pullman and Johnson 2002), P. pinaster (Miguel et al 2004;Park et al 2006), P. pinea (Carneros et al 2009, P. radiata (Hargreaves et al 2009), P. halepensis (Montalban et al 2013), hybrid P. elliottii × P. caribaea (Nunes et al 2018) and P. massoniana (Xia et al 2021;Chen et al 2023). The results described the influence of genotype on EC initiation rates, and future studies could explore a wider range of seed family at the initiation stage.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…This study showed that various seed families exhibited significantly different capacities in initiating EC, with range 1.11-27.78%, and family 7# was more responsive than families 27# and 30#. Similar significant differences in EC initiation capacity among different pine families were also observed in P. elliottii (Liao and Amerson 1995a;Liao and Amerson 1995b;Yang et al 2020), P. taeda (Tang et al 2001;Pullman and Johnson 2002), P. pinaster (Miguel et al 2004;Park et al 2006), P. pinea (Carneros et al 2009, P. radiata (Hargreaves et al 2009), P. halepensis (Montalban et al 2013), hybrid P. elliottii × P. caribaea (Nunes et al 2018) and P. massoniana (Xia et al 2021;Chen et al 2023). The results described the influence of genotype on EC initiation rates, and future studies could explore a wider range of seed family at the initiation stage.…”
Section: Discussionmentioning
confidence: 57%
“…tinctorius and Boletus edulis (Wang et al 2015). And Zheng et al (2003), Zhu et al (2010) and Chen et al (2023) showed that using ectomycorrhizal fungi Pis. orientalis can promote plant development in P. massoniana.…”
Section: And Sun Et Al (2019)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, these factors contribute to the inefficiency of Prince Rupprecht's larch breeding. The rapid progress in plant somatic embryogenesis has surmounted numerous challenges encountered in conventional sexual reproduction breeding methods, paving the path for the advancement of effective gene transfer technology and widespread propagation of new, high-performing clonal populations [7][8][9][10]. Research on somatic embryogenesis techniques in Pinus species commenced with the initial observation of embryo-like structures in Banks pine (Pinus banksiana) documented in 1976 [11].…”
Section: Introductionmentioning
confidence: 99%